"Everything on the internet can be saved": Archive Team, Tumblr and the cultural significance of web archiving. Issue 1 (3rd April 2022) - Ogden, Jessica
Abstract: This article frames the cultural significance of web archiving through an ethnographic study of Archive Team and their efforts to archive "Not Safe for Work" posts on the popular social media platform, Tumblr. This research first sheds light on the origins and organisation of Archive Team, a long-running site of web archiving and "loose collective" of volunteers dedicated to saving websites in danger of going offline. I outline two Archive Team "tenets of practice" that reflect and frame an approach to web archiving centred on cultural values dedicated to the preservation of access. Using examples from their efforts to archive Tumblr NSFW, I examine how the entanglement of practice, participants and platform resistance ultimately shapes what was deemed worth saving (and conversely, not). I argue that web archiving is a transformative force that requires attentiveness to who is archiving, but also the cultural dimensions of practice that inform everyday decisions about how the Web is "saved."